2021
DOI: 10.2147/dmso.s304164
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cut-Off Values of Visceral Fat Area for Predicting Metabolic Syndrome Among Type 2 Diabetes Patients in Ningbo, China

Abstract: Objective To examine the optimal cut-off values of visceral fat area (VFA) for predicting metabolic syndrome (MetS) among type 2 diabetes (T2D) patients in Ningbo China. Methods A total of 1017 subjects were selected from T2D patients who accepted standardized management by the National Standardized Metabolic Disease Management Center at Ningbo First Hospital from March 2018 to January 2020. Demography and medical information were collected through questionnaires. Regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“… 29 Studies have shown a high correlation of T2DM with obesity, especially visceral fat. 30 , 31 WC or BMI has been the classic index for visceral fat, accounting for the factor of obesity in patients, but WC is difficult to distinguish between visceral fat and subcutaneous fat, and BMI has limitations in viewing body composition. 32 , 33 As the number of non-obese T2DM patients increased, studies have aimed to find a more comprehensive index for predicting T2DM.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Studies have shown a high correlation of T2DM with obesity, especially visceral fat. 30 , 31 WC or BMI has been the classic index for visceral fat, accounting for the factor of obesity in patients, but WC is difficult to distinguish between visceral fat and subcutaneous fat, and BMI has limitations in viewing body composition. 32 , 33 As the number of non-obese T2DM patients increased, studies have aimed to find a more comprehensive index for predicting T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported that visceral fat area (VFA) was superior to BMI and waist circumference to predict MS and consequently, various cutoff values of VFA have been developed according to race, gender, and age [130][131][132][133]. Furthermore, it has been shown that VFA could be an independent phenotype marker of MS in type 2 diabetic patients [134]. Based on the abovementioned points, we opined that after the KRG treatment, the trial should be continued with routine analyses of the parameters and markers until the gut microbial profile is restored to its initial condition.…”
Section: Limitationsmentioning
confidence: 99%
“…5,[8][9][10][11] Obesity is usually measured using several indicators such as body mass index (BMI), waist circumference (WC), waist-to-hip ratio, and body fat mass, however, these indicators are unable to accurately distinguish between VAT and subcutaneous adipose tissue. 12 At present, although magnetic resonance imaging (MRI) and computed tomography (CT) are the gold standard to directly measure VAT, these techniques are not feasible because of consuming time, expense, and radioactivity. 12 Recently, visceral fat area (VFA), measured by the bioelectrical impedance analysis (BIA), has been recognized as a noninvasive, relatively accurate, and low-cost method of quantifying VAT.…”
Section: Introductionmentioning
confidence: 99%
“…12 At present, although magnetic resonance imaging (MRI) and computed tomography (CT) are the gold standard to directly measure VAT, these techniques are not feasible because of consuming time, expense, and radioactivity. 12 Recently, visceral fat area (VFA), measured by the bioelectrical impedance analysis (BIA), has been recognized as a noninvasive, relatively accurate, and low-cost method of quantifying VAT. 12 Studies have demonstrated that VFA level may be strongly associated with IR, inflammation, oxidative stress, metabolic syndrome (MetS), hyperlipidemia, diabetes and its vascular complications including hypertension, cardiovascular disease, diabetic retinopathy (DR), albuminuria, and cardiovascular autonomic dysfunction (one of the main types of diabetic neuropathy), 2,4,[12][13][14] all of which play pivotal roles in the pathogenesis of DPN, 1 suggesting indirectly that VFA also appears to play a crucial role in the development of DNP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation